Change in Teacher-Student Relationship Quality during a Tier-One Character Education Intervention - Garwood, Justin D. (Advances in Social Sciences Research Journal, 2024)
The rise in students’ mental health struggles and declining rates of prosocial behavior in schools has resulted in increased attention on the social, emotional, and behavioral aspects of schooling. Within the broader category of social-emotional learning, character education includes a focus on students’ intrinsic values and ways of thinking related to achieving their goals and developing personal relationships. One increasingly popular, yet under-researched, character education program for school-aged students is the Positivity Project (P2). The P2 program is a universal professional development intervention focused on the 24 unique character strengths from positive psychology. The purpose of the current study was to implement a quasi-experimental design to examine the association between teachers’ use of P2 and changes in teacher-student relationship quality. Results suggested significant effects, with increases in closeness and decreases in conflict, yielding moderate effect sizes. Implications for practice and research are discussed.